Aplicação do Conceito de KPI no ensino de Matemática - Zahner, Henrique Kops (2021)
Brazil has historically been ranked lower and lower when it comes to the PISA (Programme for International Student Assessment) index that evaluates the performance of the country’s students in mathematics. Based on it and considering that the National Common Curriculum Basis (or, the acronym in Portuguese, BNCC from Base Nacional Comum Curricular) sets that the learning of mathematics acquired by the students from the final years of elementary school, needs to be related to practical issues, that is, to aspects of reality, so it is suggested that the use of the KPI’s (Key Performance Indicator) concept as a tool to assist in this matter. KPI, on the other hand, is a numerical indicator that brings us, even graphically, relevant information about the performance of a business process, so it is important for the student’s development, as a future worker, having knowledge about the subject. It is also possible to extrapolate the concept, bringing other indicators more related to the daily life of a citizen, such as HDI (Human Development Index), IDEB (Basic Education Development Index), among countless others that are assessed by the government, based on surveys and data collection promoted by several organizations, such as the IBGE (Brazilian Institute of Geography and Statistics), for example. Thus, knowing how mathematics is fundamental for the indicators to be generated and interpreted, the student starts to understand the importance of this discipline for practical applications and promote greater awareness of the reality in which it is inserted, showing the importance of mathematics and its due protagonism, ceasing to be a “mere academic formality” as some think students, but rather a powerful tool for their development as a person.